1981
DOI: 10.1055/s-2008-1059657
|View full text |Cite
|
Sign up to set email alerts
|

NEUROMYOPATHY AND VITAMIN E DEFICIENCY in MAN1

Abstract: A 12-year-old boy, born of a consanguineous marriage, had ataxia, sensory neuropathy, generalized muscle hypotrophy and a lower serum vitamin E level. Two of his relatives had died of a clinically similar disorder in their late adolescence. Morphologically, his striated muscle fibers and Schwann cells of his sural nerve contained numerous autofluorescent acid phosphatase-positive lipopigments which, by electron microscopy, consisted of a finely granular matrix surrounded by a trilaminar membrane. These lysosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1
3

Year Published

1984
1984
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(49 citation statements)
references
References 3 publications
1
44
1
3
Order By: Relevance
“…Whether symptomatic PEI may be triggered in certain circumstances, such as infection, concurrent to existing pre-disposing factors, remains a possible explanation for subacute development of symptoms as was the case here. It is possible the myopathic features on EMG may have been related to the vitamin D deficiency, although myopathy has also rarely been reported with vitamin E deficiency [5]. Also, it is possible the weakness presented by this patient was partly myopathic in origin and that the motor improvement relates predominantly to supplementation in vitamin D rather than vitamin E. Our patient showed, despite clinical improvement, no evidence of electrophysiological amelioration, in contrast to previous cases described.…”
Section: Discussioncontrasting
confidence: 55%
“…Whether symptomatic PEI may be triggered in certain circumstances, such as infection, concurrent to existing pre-disposing factors, remains a possible explanation for subacute development of symptoms as was the case here. It is possible the myopathic features on EMG may have been related to the vitamin D deficiency, although myopathy has also rarely been reported with vitamin E deficiency [5]. Also, it is possible the weakness presented by this patient was partly myopathic in origin and that the motor improvement relates predominantly to supplementation in vitamin D rather than vitamin E. Our patient showed, despite clinical improvement, no evidence of electrophysiological amelioration, in contrast to previous cases described.…”
Section: Discussioncontrasting
confidence: 55%
“…Burck et al (1981) also reported a similar finding in a patient of vitamin E deficiency. This change resembles that induced by denervation (Parry and Montpetit 1978).…”
Section: Electron Microscopic Findingssupporting
confidence: 66%
“…The authors describe a 12-year-old boy with progressive cerebellar ataxia and a low serum vitamin E level (Burck et al, 1981). Other cases were reported before 1993; Ben Hamida et al (1993) described eight new patients belonging to two Tunisian consanguineous families.…”
Section: Introductionmentioning
confidence: 98%
“…Ataxia with vitamin E deficiency (AVED) was first described by Burck et al (1981). The authors describe a 12-year-old boy with progressive cerebellar ataxia and a low serum vitamin E level (Burck et al, 1981).…”
Section: Introductionmentioning
confidence: 99%